Osteoporosis in women: "treatment or prevention?". Physical exercise as a preventive measure (Revista horizonte, 2011)
Â This article reviews the preventive role of physical exercise in osteoporosis, with an especial focus on woman. Also, this review incorporate topic such as osteogenesis, problems associated to a bad nutrition, little exercise (or too much), amenorrhea. It describes physiological process in relation to bone metabolism. As a conclusion, physical exercise can be a protective factor in osteoporosis, independent of other factors.Â Â Â